Impact of Lockdown on Libraries and Library Professionals: A Case Study of Maharashtra - Naikwadi, V. A.; Sankpal, D. P. (Journal of Information and Knowledge, 2020)
Covid-19 Pandemic is an infectious disease that has affected the routine life of humans. Similarly, the education system including teaching and learning process has dramatically changed. This has impacted the routine of teachers and students. In the education system, role of librarians and libraries is crucial, in terms of providing quality services to meet the information needs of users. This study surveyed impact of ‘Pandemic COVID-19’ on Library Professionals. The Study also attempted to understand their experience about working from home, technologies and tools used, as well as, to identify social contributions in this crisis by library professionals. This study has considered 162 responses from various districts of Maharashtra state. The study also discusses the problems such as lack of Internet connection, difficulties, challenges faced by Library Professionals.